Penambahan Ekstrak Bawang Putih pada Edible coating Pati Singkong dan Tepung Cangkang Telur Terhadap Masa Simpan Cabai Merah - Siti Nurhalimah; Lisania Amanah; Erna Puspasari; Wilna Iznilillah (JURNAL AGROINDUSTRI HALAL, 2025)
Red chili is a horticultural product that has a short shelf life at room temperature, one of which is due to microbial contamination. This is because metabolic activities such as respiration still occur after the product is harvested. Therefore, the application of Edible Coating is an alternative to extend the shelf life of red chili. This study aims to study the effect of different concentrations of garlic extract on weight loss, TPC value, and sensory quality of red chili. Randomized Block Design (RAK) 1 factor for weight loss parameters, TPC value, sensory quality with four treatment levels consisting of A1 (0%), A2 (3%), A3 (6%), A4 (9%). The results showed that differences in garlic extract concentrations affected the weight loss values ​​around 8.52%-2.16%, the TPC values ​​ranging from 6.93 to 5.17 Log CFU/g, the sensory quality of red color, slightly complex and smooth texture, and non-rotten aroma in red chilies during a 9-day storage period at room temperature.